Anaerobic co-digestion of industrial landfill leachate and glycerin: methanogenic potential, organic matter removal and process optimization. Issue 20 (5th September 2020) - de Castro, Thiago Morais; Torres, Douglas Guedes Batista; Arantes, Eudes José; de Carvalho, Karina Querne; Passig, Fernando Hermes; Christ, Divair; Gotardo, Jackeline Tatiane; Gomes, Simone Damasceno
ABSTRACT: The objective of this study was to evaluate the performance of the anaerobic co-digestion of different concentrations of industrial landfill leachate associated with crude residual glycerin, in relation to the methanogenic potential, COD removal, accumulated methane production, the effects of the factors (food/microorganism ratio and percentage of glycerin added to the leachate) and their interactions on kinetic parameters of methane production (CH4 ) using the modified Gompertz model. Co-digestion tests were carried out in bench scale (400 mL of useful volume) under batch mode at 30 ± 1°C during 30-day incubation of anaerobic sewage sludge as inoculum. The parameters glycerin addition to the leachate (v/v) (0%, 1.5%, 5%, 8.5% and 10%) and F / M ratio (0.3, 0.5, 1, 1.5 and 1.7) were investigated using Central Composite Rotational Design method (CCRD). The results indicated significant effect to the response variables: methanogenic potential, COD removal, accumulated production of CH4 and maximum estimated production of CH4, considering a confidence interval of 95% ( p  < .05). The ideal mixture of 95.13% of leachate with 4.87% of raw glycerin was obtained by desirability test to F/M of 1.61 gCOD of substrate per gVSS (volatile suspended solids) of sludge. Methanogenic potential was 0.19 LN CH4 gTVSrem −1, and the average removal of COD was 92%, resulting in accumulated production and maximum estimated production of CH4 of 74 and 80 mL, respectively. It was noted that the process of co-digestion of the industrial landfill leachate with the crude residual glycerin is promising, due to is potential of complementing and balancing organic materials, nutrients and other components that influence the biological process. Abbreviations: AN: ammoniacal nitrogen; BMP: biochemical methane potential; CCRD: central composite rotational design; COD: chemical oxygen demand; F / M ratio: food/microorganism ratio; FSS: fixed suspended solids; NTP: normal temperature and pressure; TSS: total suspended solids; TA: total alkalinity; TFS: total fixed solids; TKN: total Kjeldahl nitrogen; TP: total phosphorus; TS: total solids; TVA: total volatile acids; TVS: total volatile solids; VSS: volatile suspended solids; WWTP: wastewater treatment plant GRAPHICAL ABSTRACT: